2017
DOI: 10.3847/1538-4357/aa68e5
|View full text |Cite
|
Sign up to set email alerts
|

Log-normal Star Formation Histories in Simulated and Observed Galaxies

Abstract: Gladders et al. have recently suggested that the star formation histories (SFHs) of individual galaxies are characterized by a log-normal function in time, implying a slow decline rather than rapid quenching. We test their conjecture on theoretical SFHs from the cosmological simulation Illustris and on observationally inferred SFHs. While the log-normal form necessarily ignores short-lived features such as starbursts, it fits the overall shape of the majority of SFHs very well. In particular, 85% of the cumula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 154 publications
(289 reference statements)
8
108
0
Order By: Relevance
“…A number of explanations for this discrepancy have been suggested in the literature, such as incorrect stel-lar mass measurements, dust corrections, a variable IMF, or incorrect inferred metallicities (Yu & Wang 2016). The inferred CSFRD is also in tension with that produced by recent numerical simulations, which tend to underestimate the normalisation at cosmic noon (Davé 2008;Furlong et al 2015;Diemer et al 2017). We here explore the impact on this discrepancy of updated SFR calibrations.…”
Section: Introductionmentioning
confidence: 88%
“…A number of explanations for this discrepancy have been suggested in the literature, such as incorrect stel-lar mass measurements, dust corrections, a variable IMF, or incorrect inferred metallicities (Yu & Wang 2016). The inferred CSFRD is also in tension with that produced by recent numerical simulations, which tend to underestimate the normalisation at cosmic noon (Davé 2008;Furlong et al 2015;Diemer et al 2017). We here explore the impact on this discrepancy of updated SFR calibrations.…”
Section: Introductionmentioning
confidence: 88%
“…In total, there are 29,203 galaxies in the Illustris simulation with stellar mass greater than 10 9 M ⊙ (Diemer et al 2017).…”
Section: Construction Of the Mock Sfhsmentioning
confidence: 99%
“…The change in SFR, and thus in SFR79 due to maintaining a constant ∆SFR 800Myr , is negligible. Right panel: the relation between the SFR79-SFR9/M * in logarithmic space for the best-fit log-normal SFHs of the SF galaxies (sSFR7 > 10 −2 [Gyr −1 ]) selected from Illustris from Diemer et al (2017). Using the best-fit log-normal SFHs smooths out all short-term variations of the SFHs.…”
Section: The Evolution Of Sfms Indicated By the Changementioning
confidence: 99%
“…All these shapes can be useful to describe the star-formation history averaged over the entire population of a galaxy survey; however, chemical and photometric data require to differentiate between disc-like and spheroid-like star-formation histories, making the parametric models for each class (e.g., see Fig. 2 in Diemer et al 2017) essentially indistinguishable from our simple adopted shapes. For example, to describe the history of a starforming disc the timescale of the early rise has to be much faster than that of the late decline, to mirror the exponential model of Eq.…”
Section: Star-formation History Of Individual Galaxiesmentioning
confidence: 99%
“…A classic way involves the so-called 'delayed exponential' model M ⋆ (τ ) ∝ τ κ e −τ /τ⋆ , with two parameters κ and τ ⋆ controlling the early powerlaw rise and the late exponential decline. More recently, analogy with the behavior of the cosmic SFR density (see Gladders et al 2013) and indications from numerical simulations (see Diemer et al 2017) have suggested a lognormal shapeṀ…”
Section: Star-formation History Of Individual Galaxiesmentioning
confidence: 99%